Statistical analysis-based assessment of well water quality in bottomland area – Hai Lang district, Quang Tri province - Hữu, Nguyễn Trọng; Dũng, Mai Xuân; Khoa, Nguyễn Trường; Nam, Nguyễn Hữu; Hợp, Nguyễn Văn (Hue University Journal of Science: Natural Science, 2019)
The data of well water quality monitoring (drilled and dug wells) in six communes of the bottomland area, Hai Lang district, Quang Tri province, including Hai Thanh, Hai Duong, Hai Vinh, Hai Ba, Hai Que, and Hai Hoa from 2015 to 2017 with the frequency of once per year (April or May annually) were collected. On the basis of data and the results obtained from sampling and analysis of well water quality at three sites in three communes (Hai Ba, Hai Que, and Hai Hoa) between 2018 and 2019 with the frequency of once per year (October 2018 or May 2019), the well water quality in the area was assessed through 12 parameters: pH, turbidity, TDS, COD, Cl–, N–NH4+, N–NO3–, N–NO2–, SO42–, total dissolved iron (Fe), total dissolved manganese (Mn), and total coliform. Analysis of variance, principal component analysis (PCA), and agglomerate hierarchical clustering (AHC) were also applied to assess the spatial and temporal variation of well water quality. The area was divided into three sub-area with different well water quality: Sub-area I including Hai Duong and Hai Vinh communes considerably polluted with organics (high COD); Sub-area II (Hai Thanh and Hai Hoa communes) contaminated with iron (high Fe and low pH); and Sub-area III (Hai Ba and Hai Que communes) much conatminated with salts (high TDS, Cl–, SO42–), Mn, and total coliform.